Penerapan Manajemen Risiko dalam Pengelolaan Satuan Pendidikan di Indonesia - Fadilatul Istiqamah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This article discusses the Application of Risk Management in the Management of Educational Institutions in Indonesia, which aims to analyze the importance of risk management in maintaining the sustainability and quality of educational institutions. In facing various challenges, both internal, such as limited resources and managerial errors, and external, such as policy changes, educational institutions are required to have an effective and integrated risk management system. This study uses a library research method by examining various sources such as scientific journals, books, and relevant laws and regulations. The results show that the systematic application of risk management through the stages of identification, analysis, mitigation, implementation, and evaluation can help educational institutions anticipate potential disruptions and improve management efficiency. In addition, the successful implementation of risk management is greatly influenced by human resource competencies, risk awareness, and stakeholder support. However, in Indonesia, its implementation still faces obstacles in the form of a lack of understanding among managers, limited resources, and suboptimal integration into the school management system. Therefore, it is necessary to strengthen managerial capacity, provide continuous training, and obtain government policy support so that risk management risk management can be implemented effectively, sustainably, and capable of improving the quality of national education.